Resummed kinetic field theory: using mesoscopic particle hydrodynamics to describe baryonic matter in a cosmological framework - Geiß, Daniel; Lilow, Robert; Fabis, Felix; Bartelmann, Matthias (Journal of cosmology and astroparticle physics, 2019)
We present a new analytical description of baryonic matter in a cosmological framework, using the formalism of “Kinetic Field Theory” (KFT)—a statistical field theory approach to structure formation based on the dynamics of classical particles. So far, only the purely gravitational dynamics of dark matter had been considered in KFT, but an accurate description of cosmic structure formation requires to also take into account the baryonic gas dynamics. In this paper, we propose to achieve this by incorporating an effective mesoscopic particle model of hydrodynamics into the recently developed framework of Resummed KFT. Our main result is the baryonic density contrast power spectrum computed to lowest perturbative order, assuming a simplified isothermal fluid model. Compared to the spectrum of dark matter, the baryonic spectrum shows a suppression of power as well as an oscillatory behaviour associated with sound waves on scales smaller than the Jeans length. We further compare our result to the linear spectrum of an isothermal fluid obtained from Eulerian perturbation theory (EPT), finding good quantitative agreement within the approximations we made in the EPT calculation. A subsequent paper will resolve the problem of coupling both dark and baryonic matter, to gain a full model of cosmic matter. Applying the mesoscopic particle approach to more general ideal or viscous fluids will also be subject of upcoming work.